Techno – Economic Analysis for Biorefinery - Gede Arya Rachman; Syukri M. Nur (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
This comprehensive study explores the implementation of technical-economic analysis in the context of biorefinery, a key solution in the transition to a sustainable bio-based economy. The global biorefinery industry has witnessed significant growth, with a market value reaching USD 614.25 billion in 2022 and projected to grow at a CAGR of 8.2% through 2030. However, increasing energy consumption in biorefinery operations has raised concerns about economic efficiency and sustainability, underscoring the critical role of technical-economic analysis. This study adopts a bibliometric approach, integrating quantitative and qualitative analysis to systematically examine the implementation of technical-economic analysis in biorefinery. The study offers several key findings: (1) the chemical, manufacturing, and food processing sectors account for a significant share of energy consumption, with a potential reduction of 30-40% through biorefinery implementation; (2) the integration of technical-economic analysis in biorefinery operations has resulted in a 40% increase in biomass conversion efficiency, a 35% increase in resource utilization, and a 45% reduction in waste generation, while delivering an annual ROI of 22%; (3) the application of technical-economic analysis has resulted in substantial cost savings, energy efficiency, and reduced environmental impacts. The study also identifies challenges, such as high initial investment and potential resistance to change, as well as the need for further research on the scalability and transferability of the proposed framework. In addition, the findings highlight important policy and regulatory implications, emphasizing the need for targeted incentives and industry-specific guidelines to promote the integration of technical-economic analysis in biorefinery projects. This study provides a comprehensive understanding of the critical role of technical-economic analysis in transforming the biorefinery industry, paving the way for a more sustainable and resilient bio-based economy. The key insights and practical recommendations presented in this study can serve as valuable guidance for industry practitioners, policy makers, and researchers in advancing the adoption of this transformative strategy.